Indirect intrusions about World War Two in survivor offspring: a qualitative thematic content analysis - Patricia Dashorst; Trudy Mooren; Wencke Donath; Anne Blonk; Rolf Kleber; Peter de Jong; Rafaele Huntjens (European Journal of Psychotraumatology)
Background: A proportion of Dutch World War Two (WWII) survivor offspring reports intrusions about a war they have not experienced themselves. Knowledge about the content of these intrusions may provide an in-depth understanding of the themes impacting the mental health of offspring and the intergenerational consequences of parental traumatic WWII events. Therefore, this study used a qualitative approach to examine the core themes of indirect intrusions reported by survivor offspring.Methods: Participants (N = 41) were post-war-born offspring of WWII survivors. They were in treatment in one of two national clinics specialized in the treatment of war victims. We conducted an inductive thematic analysis of the written descriptions of indirect intrusions reported in the offspring sample and related to WWII survivor experiences.Results: The analysis indicated the following themes: Cruelty (with several subthemes), Perspective (first or third person), Sensory perceptions, and Emotions.Conclusions: Offspring mostly described intrusions about WWII as visual cruel images from a first-person perspective, provoking distress and other strong emotions. Indirect intrusions may signify intergenerational consequences of parental traumatic events. Therefore, special attention is needed to the presence and content of indirect intrusions among offspring of survivors of wars or other traumatic events.